MIXING OF CO2 IN SURFICIAL ENVIRONMENTS AS RECORDED BY THE CONCENTRATION AND δ13C VALUES OF THE FE(CO3)OH COMPONENT IN GOETHITE - Yapp C.J. (My University, 2001)
Measured values of mol fraction (X) and δ13C in the Fe(CO3)OH component of 49 samples of goethite (α-FeOOH) from a wide variety of environments range from 0.0015 to 0.0182 and from -21.7 to +3.3%%, respectively. The distribution of δ13C values appears to be bimodal. δ13C values are > -12%% for marine hydrothermal goethites and continental goethites crystallized as secondary minerals in host rocks. With the exception of a young soil (DRR), δ13C is < -14%% for pedogenic/oolitic and bog ore goethites.Values of X and temperature determined for pedogenic goethite can be combined with the modern, global relation between soil respiration (Q) and average annual temperature to estimate diffusion coefficients (DS) for steady-state Fickian diffusion of CO2 in soils. Although there is considerable scatter in the relationship between Q and T, an illustrative calculation for a characteristic depth of 0.20 m, yields calculated values of DS that range from about 0.002 to 0.011 cm2/s among seven goethite-bearing soils.Steady-state diffusive transport of CO2 in soils with one in situ source of CO2 (oxidation of organic matter) yields a soil CO2 mixing equation for two isotopically distinct CO2 components (oxidized organic matter and atmospheric CO2). With pedogenic goethite as a proxy for the soil CO2, the positive slope of this two-component mixing equation can be used for determinations of CO2 pressures in the Earth's atmosphere. If, however, dissolution of carbonates is concurrent with goethite crystallization, the mixing equation (at z # z*) becomes three-component with a negative slope that precludes estimates of atmospheric Pco2. An example is the DRR soil in which in situ, low-pH dissolution of relict, marine invertebrate fossils produced a negative mixing slope and goethite δ13C values that range from -14.2 to -4.1%%. These results indicate that only goethites which crystallized in carbonate-free soils (highly leached or formed on initially carbonate-poor rocks) should be used to deduce ancient atmospheric CO2 pressures.Addition of CO2 from dissolution of carbonates also appears to explain the range of δ13C values of most of the secondary continental goethites presumably formed in saturated groundwater systems. However, some of the variation of X and δ13C of the Fe(CO3)OH component in these goethites may be a consequence of variations in ambient pH. This possible dependence on pH seems to be manifested in a suite of goethites pseudomorphed after pyrite in a marine limestone.